1976
DOI: 10.1042/bj1570289
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of immobilized baker's-yeast glucose 6-phosphate dehydrogenase attached to modified sepharose and sephadex and a comparison of the properties of these preparations with those of the soluble enzyme

Abstract: 1. Glucose 6-phosphate dehydrogenase (D-glucose 6-phosphate-NADP+ oxidoreductase, EC 1.1.1.49) from baker's yeast (Saccharomyces cerevisiae) was immobilized on CNBr-activated Sepharose 4B with retention of about 3% of enzyme activity. This uncharged preparation was stable for up to 4 months when stored in borate buffer, pH7.6, at 4 degrees C. 2. Stable enzyme preparations with negative or positive overall charge were made by adding valine or ethylenediamine to the CNBr-activated Sepharose 4B 30min after additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1977
1977
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…Regarding the immobilization on agarose based matrices, Anwar et al . immobilized a baker's yeast GDH on cyanogen bromide‐sepharose obtaining a retained activity of 3% . Persson et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the immobilization on agarose based matrices, Anwar et al . immobilized a baker's yeast GDH on cyanogen bromide‐sepharose obtaining a retained activity of 3% . Persson et al .…”
Section: Resultsmentioning
confidence: 99%
“…42 Regarding the immobilization on agarose based matrices, Anwar et al immobilized a baker's yeast GDH on cyanogen bromide-sepharose obtaining a retained activity of 3%. 47 Persson et al purified a GDH from Bacillus subtilis by immobilizing it on thiopropyl-sepharose and recovered up to 65% of the initial activity. 48 However, as far as the authors know, this is the first time that GDH has been covalently co-immobilized with P450 BM3.…”
Section: Co-immobilization Of P450 Bm3 and Glucose Dehydrogenasementioning
confidence: 99%
“…Some results found in the literature show that the time stability of immobilized G6PDH depends strongly on immobilization conditions. For instance Goheer et al found that the enzyme retained full activity over a period of 4 months when covalently attached to CNBr-activated Sepharose 4B; but when attached to CNBr-activated Sephadex G-25 for 2 weeks lost all of its activity on storage at room temperature and 40% of its activity on storage at 4 • C [40]. Allcock et al compared G6PDH in solution and G6PDH immobilized on polyphosphazene/alumina particles [41].…”
Section: Covalently Immobilized G6pdh On Sepabeads ® Ec-hamentioning
confidence: 97%
“…At higher temperature of 37°C, a sharp decrease in response was observed. Previously, Goheer et al (11) have reported on the effect of temperature on free and immobilized G6PDH. These authors found that the soluble enzyme preparations were rapidly deactivated at 37°C, retaining only 20% of the original activity after 15-min incubation.…”
Section: Optimization Of G6p Biosensormentioning
confidence: 99%